Diagnostic relevance of urinary steroid profiles on ovarian granulosa cell tumors: two case reports - Bufa, Anita (J Med Case Rep, 2017)
BACKGROUND: Granulosa cell tumor of the ovary is the most frequent sex cord stromal tumor and represents 2 to 5% of all primary ovarian cancers. Ovarian granulosa cell tumor is a malignant tumor with slow progression and in some cases this tumor is hormonally active. The recurrence of granulosa cell tumor often happens after 5 years. CASE PRESENTATION: We describe two cases of postmenopausal women with adult-type granulosa cell tumors of the ovary. Patient 1 is a 49-year-old European woman with a recurrent tumor; patient 2 is a 55-year-old European woman without recurrence of tumor. Urinary steroid profiles of patient 1 were monitored during a 5-year period starting from before an operation (13 samples). In patient 2, the urinary steroid profiles were monitored during a 3-year period starting from after an operation (six samples). The 24-hour urinary samples were examined and the urinary concentration of 20 androgen, progesterone, and corticoid metabolites was quantitatively determined by gas chromatography-mass spectrometry with selected ion-monitoring mode. CONCLUSIONS: Based on these cases a correlation could be observed between increased levels of the urinary steroids and the recurrence of ovarian granulosa cell tumor; therefore, we concluded that a urinary steroid profile could be a more effective method to follow-up such patients compared to the traditional serum hormones determinations supplemented with conventional tumor markers.